Gender Differences in How Leaders Determine Succession Potential: The Role of Interpersonal Fit With Followers - Rink, Floor; Stoker, Janka I.; Ryan, Michelle K.; Steffens, Niklas K.; Nederveen Pieterse, Anne (Frontiers in Psychology, 2019)
This paper examined the existence of gender differences in the degree to which leader’s perceptions of successor potential is influenced by interpersonal fit. In Study 1 (n = 97 leaders and n = 280 followers) multi-source field data revealed that for male leaders, ratings of followers’ potential as successors were positively related to interpersonal fit, measured by the degree to which followers’ saw their leadership as being close and interpersonal (i.e., being coaching, transformational and leading by example). For female leaders, these relationships were absent, suggesting that they are less driven by interpersonal fit. In Study 2 (n = 311 leaders) a scenario study provided causal evidence that male leaders rated potential successors more positively when they perceived greater interpersonal fit with followers, whereas female leaders’ successor ratings where not informed by fit perceptions. We discuss the theoretical and practical implications for gendered leadership successor perceptions in organizations.